M22 Does a Nurse-Led Non Invasive Ventilation (NIV) Service improve patient outcomes?. (12th November 2015) - Mainman, H; Chambers, S; Curtis, HJ
Abstract : Introduction and objectives: Non-invasive ventilation (NIV) has been shown to reduce in-patient mortality in AECOPD from 20 to 10%. In 2011 national data revealed that there were multifactorial failures in effective NIV service provision, with a 26% in-patient mortality rate. Local audit data in 2012 showed our in-patient mortality was 40% for all patients treated with NIV compared to a national rate of 30%. There was evidence of missed patients and delays to treatments. Could a nurse-led NIV service improve upon this? Methods: We set up a dedicated 24/7 nurse-led service with portable NIV machines and allocated respiratory ward beds in December 2013. The nurse would aim to be involved in all AECOPD admissions from the outset, with support from acute medical team. All aspects of clinical care were prospectively collected including nursing workload. Results: More patients received NIV with an improved success rate and reduced in-patient mortality rate. Mortality fell to 12% by summer 2014, and was 0% in patients with pH 7.25–7.35. Quality indicators also improved e.g. failure planning, in-put from respiratory team and consultants (See Table 1). Although survival rates were maintained over winter 2014/15, quality indicators slipped, due to nursing pressures across our trust, which compromised the service. During this period the NIV-nurse had extra or alternative duties on 28% of the shifts. As a consequence 6 patients were treated on Intensive care and 3 operations were cancelled. Conclusions: The nurse-led service has dramatically improved survival outcomes and the quality of our NIV service. We believe this to be due to a dedicated nurse-led model as opposed to a traditional physiotherapy service. But this model may be leaving our service open to the external pressures in nursing numbers across our trust. Via our robust data collection and rolling analysis, we have been able to influence decision makers into not "pulling" the NIV nurse to alternative duties and compromising our successful service.